(untitled) (Acta Scientiarum. Agronomy, 2017)
The aim of this work was to verify the efficiency of the anticipated selection of superior plants in intrapopulation breeding of passion fruit. The experiment was conducted at the Mato Grosso State University experimental area. Eight populations were evaluated. Planting was carried out in August 2010 following the randomized blocks experimental design, with ten repeats and ten plants per plot. The production characteristics of mass and number of fruits were evaluated from data obtained from two cultivation periods, the first year and the full two-year cycle of culture. Estimates of genetic parameters indicate the possibility of selection gains. The accuracies of fruit production, fruit number and fruit mass characteristics had high magnitude, independent of the selection cycle. Coincidence index estimates were high for all characteristics. Based on the results, early selection (first year) was efficient and reduced the time of selection for the best plants and can be used for passion fruit breeding.